2020
DOI: 10.1039/c9nj06161d
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopic detection of ketene formation from carbene and CO sources: an amide synthesis

Abstract: An effective methodology to detect the highly reactive ketene intermediate, which is formed in situ during the course of organic transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The reactants were recovered as such. Knowing that palladium and copper catalysts act well as catalysts for carbene generation from diazo compounds, we continued our studies with these catalysts. We screened different Pd catalysts (5 mol %) to optimize the reaction conditions (Table , entries 2–5). On using Pd 2 (dba) 3 as a catalyst, the desired product 3a was not observed even after 12 h. So, we heated the reaction mixture at 45 °C and yielded 40% of 3a , whereas Pd­(OAc) 2 , PdCl 2 , and Pd­(OTf) 2 gave only 19–38% of the expected α-acyloxy ester ( 3a ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactants were recovered as such. Knowing that palladium and copper catalysts act well as catalysts for carbene generation from diazo compounds, we continued our studies with these catalysts. We screened different Pd catalysts (5 mol %) to optimize the reaction conditions (Table , entries 2–5). On using Pd 2 (dba) 3 as a catalyst, the desired product 3a was not observed even after 12 h. So, we heated the reaction mixture at 45 °C and yielded 40% of 3a , whereas Pd­(OAc) 2 , PdCl 2 , and Pd­(OTf) 2 gave only 19–38% of the expected α-acyloxy ester ( 3a ).…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal-catalyzed insertion of carbene into the X–H bonds (X = C, O, N, Si) has been beneficial for the synthesis of α-amino, α-hydroxyl, α-silyl, or α-acyloxy ester derivatives over the past few decades. Wolfrom et al first introduced diazo compounds into carboxylic acids for the synthesis of α-acyloxy carbonyl compounds via a carbene insertion reaction . Tan and co-workers demonstrated catalytic enantioselective COO–H insertion of α–diazoketones into carboxylic acids with basic guanidine in the presence of Rh 2 (OAc) 4 , forming chiral guanidinium salts, which can participate in an insertion reaction of Rh carbenoids .…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, so far, Davies report of carbene insertion into the ‐OH bond of p‐tosyl sulfonic acid is the only known example in the literature for functionalization of the −OH bond of sulfonic acid. In this regard and in continuation of our research on carbene insertion reactions [67–72,81,83,86‐87] we herein report the insertion of carbene into the O−H bond of aromatic sulfonic acids using α‐diazo ester to generate the sulfonic esters.…”
Section: Introductionmentioning
confidence: 79%
“…The band at 1598 cm −1 attributable to the β-lactam did not alter after 2 h. The excess [Co 2 (CO) 8 ] bands at 2071, 2040, and 1845 cm −1 were unchanged in the reaction mixture (Figure 9). A % transmittance versus time plot 55 for the formation of ethyl (3R,4S)-2-oxo-1,3,4-triphenylazetidine-3-carboxylate at different loads of [Co 2 (CO) 8 ] is depicted in Figure 10. The IR spectroscopic observations concluded that the optimum load of [Co 2 (CO) 8 ] is 0.5 equiv producing the highest yield of the expected product.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Quantitative studies are available where IR spectroscopy is utilized to detect ketene formed by the carbonylation of diazo compounds by non-gaseous metal carbonyl [Co 2 (CO) 8 ] . [Co 2 (CO) 8 ] is known to catalyze carbonylation reactions, aza-Pauson-Khand-type reaction, , condensation and intra-molecular carbonylative cyclization, , ring-opening carbonylations, ring-opening carbonylative polymerizations, , and ring-expansion carbonylations . Hence, the use of metal carbonyl is a superior option for carbonylation of diazo compounds at mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%